2010
DOI: 10.2147/amep.s13750
|View full text |Cite
|
Sign up to set email alerts
|

Station-based deconstructed training model for teaching procedural skills to medical students: a quasi-experimental study

Abstract: BackgroundEvery procedural skill consists of some microskills. One of the effective techniques for teaching a main procedural skill is to deconstruct the skill into a series of microskills and train students on each microskill separately. When we learn microskills, we will learn the main skill also. This model can be beneficial for tuition on procedural skills.ObjectiveIn this study, we propose a stationed-based deconstructed training model for tuition of each microskill, and then we assessed the medical stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…This will help students to get formal procedural training maintained skills performance superiority over subsequent years of medical school [10]. Several studies showed that clinical skills curricula have demonstrated significant improvements in medical student confidence after implementation of formal procedural skills courses [9,11,12].…”
Section: Teaching Medical Proceduresmentioning
confidence: 99%
“…This will help students to get formal procedural training maintained skills performance superiority over subsequent years of medical school [10]. Several studies showed that clinical skills curricula have demonstrated significant improvements in medical student confidence after implementation of formal procedural skills courses [9,11,12].…”
Section: Teaching Medical Proceduresmentioning
confidence: 99%
“…Having a procedural description can assist trainees in learning complex cases by finding common features in existing knowledge [ 15 ]. It has utility in reducing the mental effort required to learn a new task by breaking it down into more approachable chunks of knowledge [ 16 , 17 ], and can improve performance of procedural skills [ 18 , 19 ]. Procedural deconstruction has even be used to guide novel training approaches such as teaching appendicectomy to a non-surgically trained space team [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 A procedure can be broken down into simpler tasks (task deconstruction) and then appropriate instruction is made available to guide the novice (instructional scaffolding). 2,3 We propose a novel use of 3-dimensional (3D) models in surgical training: stepwise models that are operable, both to demonstrate an unfolding operation as a 3D dissection guide, but also to allow for practice of the operation, with the option to practice any specific step repeatedly and in any order. The objective of this study was to develop and pilot test a process for creating reproducible stepwise surgical 3D models that are patient and surgical educator specific.…”
mentioning
confidence: 99%
“…For example, operative textbooks and dissection manuals break down surgeries into smaller steps that are put together to demonstrate the progression of the surgery 1 . A procedure can be broken down into simpler tasks (task deconstruction) and then appropriate instruction is made available to guide the novice (instructional scaffolding) 2,3 …”
mentioning
confidence: 99%